(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Cardiovascular dysfunction is often preceded by subtle changes in skin microcirculation due to disturbances in physiological homeostasis during physical or emotional stress. Early detection of these microcirculatory changes provides important insights into cardiovascular health. This project proposes a multi-sensor system integrating Electrocardiogram (ECG), Pulse Oximeter with Perfusion Index (PI), and Galvanic Skin Response (GSR) to monitor cardiac activity, vascular perfusion, and autonomic responses during stress. The Perfusion Index (PI) obtained from the pulse oximeter serves as an indicator of peripheral blood flow and microvascular perfusion, enabling better assessment of circulatory variations. Data collected from subjects before, during, and after induced stress are processed using signal processing techniques and a Multi-Layer Perceptron (MLP) algorithm to identify patterns associated with cardiovascular variations. A portable skin perfusion monitoring prototype is developed as a low-cost and scalable solution for early cardiovascular stress detection in healthcare monitoring and future long-duration space missions, with system control implemented through an Arduino platform.